Analisis Penerapan Sistem Informasi Akuntansi Persediaan Obat-Obatan dan Alat Kesehatan Pada RSU PKU Muhammadiyah Jatinom - Siti Sulistyowati; Muhamad Rifandi (CV. Ulil Albab Corp, 2023)
A hospital is a type of healthcare facility that arranges all of the inpatient, outpatient, emergency, and other types of healthcare services that patients may require. The provision of medications and medical devices for health support is one type of health service offered. This study aims to determine the implementation of the Accounting Information System for Medicines and Medical Devices at PKU Muhammadiyah Jatinom Hospital. The research employed descriptive research method with a qualitative approach which aimed to describe the object of the research by collecting data. Data collection techniques were carried out by means of direct observation, interviews, as well as documentation. Sources of data used were primary data and secondary data. Based on the results of the study it can be concluded that PKU Muhammadiyah Jatinom Hospital has implemented an Accounting Information System for Medicines and Medical Devices Supplies starting from planning the procurement of medicines and medical devices, storing medicines and medical devices, distributing medicines and medical devices, and destroying expired medicines. However, there were still weaknesses in the Accounting Information System for Medicines Supplies and Medical Devices at PKU Muhammadiyah Jatinom Hospital that have not been fully computerized. This is due to the fact that the employed SIMRS was not developed by the hospital itself, which means that many functions are still completed manually.